The combined vaccination protocol of DNA/MVA expressing Zika virus structural proteins as efficient inducer of T and B cell immune responses - Patricia Pérez; Miguel A. Martín-Acebes; Teresa Poderoso; Adrián Lázaro-Frías; Juan-Carlos Saiz; Carlos Óscar S. Sorzano; Mariano Esteban; Juan García-Arriaza (Emerging Microbes and Infections)
Zika virus (ZIKV) is a mosquito-borne pathogen with public health importance due to the high risk of its mosquito vector dissemination and the severe neurological and teratogenic sequelae associated with infection. Vaccines with broad immune specificity and control against this re-emerging virus are needed. Here, we described that mice immunized with a priming dose of a DNA plasmid mammalian expression vector encoding ZIKV prM-E antigens (DNA-ZIKV) followed by a booster dose of a modified vaccinia virus Ankara (MVA) vector expressing the same prM-E ZIKV antigens (MVA-ZIKV) induced broad, polyfunctional and long-lasting ZIKV-specific CD4+ and CD8+ T-cell immune responses, with high levels of CD4+ T follicular helper cells, together with the induction of neutralizing antibodies. All those immune parameters were significantly stronger in the heterologous DNA-ZIKV/MVA-ZIKV immunization group compared to the homologous prime/boost immunizations regimens. Collectively, these results provided an optimized immunization protocol able to induce high levels of ZIKV-specific T-cell responses, as well as neutralizing antibodies and reinforce the combined use of DNA-based vectors and MVA-ZIKV as promising prophylactic vaccination schedule against ZIKV.